The Amino Acids Glutamic Acid and Alanine in Feed Increase the Alanine Content in Gonads of the Sea Urchin Mesocentrotus nudus - Takagi, Satomi; Murata, Yuko; Koshiishi, Tomohiko; Agatsuma, Yukio (Frontiers in Marine Science, 2020)
Taste is an important trait of sea urchin quality. Highly contained alanine in gonads of the sea urchin Mesocentrotus nudus results in desirable taste. Past studies hypothesized that high levels of glutamic acid and/or alanine in feed increase the alanine content in the gonads. To identify the amino acids in feed that increase the alanine content in the gonads, the free amino acid content in the gonads of M. nudus of the following five treatment groups were compared at the start and end of the feeding experiment during May–July: sea urchins fed one of four experimental diets, in which glutamic acid (Glu S), alanine (Ala S), aspartic acid (Asp S) or glycine (Gly S) was supplemented, or a control diet without supplementation (Control). The alanine content in the gonads of Ala S increased significantly from the start. The content in the gonads of Glu S increased without significance. There was no significant difference in the alanine content in the gonads between Ala S and Glu S. The content in the gonads of Ala S was significantly higher than that of Asp S, Gly S and Control. There were no significant differences in the aspartic acid and glutamic acid contents in the gonads among treatments at the end of the experiment. The higher alanine content in the gonads of Ala S than that in Glu S indicates that direct accumulation of alanine from the feed is effective. This study first identified the amino acids in feed that are closely associated with improvement in the taste of sea urchin gonad.